Productivity of Tifton 85 grass irrigated and overseeded with winter forages - Éder Pereira Gomes; Max Emerson Rickli; Ulysses Cecato; Camila Viana Vieira Farhate; Rafael Henrique de Tonissi e B. de Goes; Elir de Oliveira (Acta Scientiarum. Animal Sciences, 2015)
Intercropping with cool season species has been used as an alternative to increase productivity off-season (fall/winter) of irrigated pastures. This study was conducted from May to October 2009 in Icaraíma, Paraná State, to evaluate the productivity and morphological composition of the Tifton 85 grass overseeded with winter forage in irrigated system. The experiment was a randomized block design with four replicates and repeated measures over time. The experimental plots consisted of five treatments, three as oats overseeding using the genotypes IAPAR 61, IPR 126, and FMS2 on Tifton 85 pasture and one as overseeding of oats combined with rye (IPR 126 + IPR 89) also on Tifton 85 grass and, finally, a control with only Tifton 85 without overseeding. The overseeding of IPR 126 oats achieved the highest cumulative productivity, 4102 kg DM ha-1, with leaf/stem ratio higher than that of exclusive Tifton 85 exclusive, 1.77 and 1.08, respectively. However, overseeding of winter forages did not increase the overall productivity of the pasture.